Evaluation of future meteorological and hydrological drought in the Rufiji basin - Fernandes, Dwayne (Department of Environmental and Geographical Science, 2025)
This research is driven by the critical need to understand the dynamics of drought patterns in the Rufiji Basin, Tanzania, under both current and future climatic scenarios. Droughts, with their profound impact on the socio-economic fabric and environmental sustainability of the region, represent a significant challenge in the Rufiji Basin, where both meteorological and hydrological droughts are prevalent. To tackle this issue, the study applies three key drought indices—the Standardized Precipitation Index (SPI), the Standardized Precipitation-Evapotranspiration Index (SPEI), and the Streamflow Drought Index (SDI)—to analyze 12-month drought events within the basin. This approach allows for a examination of drought characteristics, including their frequency, intensity, as well as its spatial distribution by the use of hydrological flux variables such as precipitation, evapotranspiration, lateral flow, and soil moisture. This research distinguished itself by segmenting the Rufiji River Basin, which encompasses four primary basins—the Great Ruaha, Kilombero, Luwegu, and Lower Rufiji—into six parts. Specifically, the Great Ruaha Basin was further divided into the Upper Great Ruaha, Lower Great Ruaha, and Little Ruaha, allowing for a more nuanced analysis of hydrological dynamics within the region. The study's goal was to ascertain the unique drought characteristics of each sub-basin. Historical climate data was sourced and downscaled from ERA5 Land, and future climate scenarios were based on simulations from 13 CORDEX Regional Climate Models (RCMs). The analyses of the SPI and SPEI utilized the CORDEX climate data in its calculation. The historical time period selected for this study was 1991-2020, aligning with the guidelines of the World Meteorological Organization (WMO). The periods designated for the near future and far future analyses were 2031-2060 and 2071- 2100, respectively. The study employed the SWAT+ hydrological model, calibrated at Stiegler's Gorge on a monthly base. The model achieved a Nash-Sutcliffe Efficiency (NSE) of 0.7 which was used to simulate historical and future streamflow projections. This calibration refined the model's peak and base flows for better simulation accuracy. Following the SWAT+ analysis, the Streamflow Drought Index (SDI) analysis was conducted to further investigate hydrological drought characteristics. The SWAT+ model also facilitated the creation of the maps to investigate predicted changes in hydrological fluxes such as precipitation, evapotranspiration, lateral flow and soil moisture. Findings from the study reveal that under both RCP 4.5 and RCP 8.5 scenarios, there is a projected increase in the intensity and frequency of meteorological droughts within some sub-basins in both the near and distant future, with a significant exacerbation during the latter period. All CORDEX models indicated an increase in temperature, especially under the RCP 8.5 scenario, with little variability of future precipitation trends. Despite common beliefs that global warming would universally increase intensity and magnitude of drought through increased evapotranspiration, modelling output suggests this trend may not hold true for all sub-basins. Regions such as the Kilombero and Lower Rufiji sub-basins, along with the vicinity of the Mtera Reservoir, are anticipated to see a rise in wetting predominantly due to future increases in precipitation. However, these areas could also encounter issues like diminished soil moisture and lateral flow if the least optimistic model projections come to pass. On the other hand, the Luwegu and Little Ruaha sub-basins emerge as particularly sensitive to increases in potential evapotranspiration and temperature and could be more likely to face heightened frequencies and intensities of droughts. These shifts hold critical implications for the ecological systems and human endeavours within these sub-basins. For example, in the Luwegu, where the Nyerere National Park is situated, changes in drought conditions could have a marked impact on wildlife and the broader ecosystem. In the Little Ruaha, critical for its wetlands, the anticipated reduction in soil moisture and lateral flow poses risks to dependent agricultural and forestry operations. This research highlights the urgent need for comprehensive water resource management and adaptive measures to counteract the negative impacts of evolving drought patterns in the Rufiji Basin, thereby protecting its natural environments and the livelihoods dependent on them.